Numerical investigation of the effect of substrate surface roughness on the performance of zigzag graphene nanoribbon field effect transistors symmetrically doped with BN - Sanaeepur, Majid; Yazdanpanah Goharrizi, Arash; Sharifi, Mohammad Javad (Beilstein Journal of Nanotechnology, 2014)
The performance of field effect transistors comprised of a zigzag graphene nanoribbon that is symmetrically doped with boron nitride (BN) as a channel material, is numerically studied for the first time. The device merit for digital applications is investigated in terms of the on-, the off- and the on/off-current ratio. Due to the strong effect of the substrate roughness on the performance of graphene devices, three common substrate materials (SiO2, BN and mica) are examined. Rough surfaces are generated by means of a Gaussian auto-correlation function. Electronic transport simulations are performed in the framework of tight-binding Hamiltonian and non-equilibrium Green's function (NEGF) formalisms. The results show that with an appropriate selection of the substrate material, the proposed devices can meet the on/off-current ratio required for future digital electronics.
Keywords: boron nitride; non-equilibrium Greens function (NEGF); on-/off-current ratio; substrate roughness; zigzag graphene nanoribbon field effect transistor (ZGNRFET)